2017
DOI: 10.1080/14786419.2017.1378216
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition of the essential oils isolated from peel of three citrus species and their mosquitocidal activity against Culex pipiens

Abstract: Three essential oils (EOs) were isolated from the peel of citrus fruits Citrus reticulata L., Citrus reticulata chinase Blanco and Citrus sinensis (L.) Osbeck (Family: Rutaceae) and evaluated against Culex pipiens L.1758 (Family: Culicidae). Chemical composition indicated that the EOs were rich in essential phytochemicals including hydrocarbons, monoterpenes and sesquiterpenes. These constituents revealed some variability among the oils displaying interesting chemotypes limonene (35-51%), 1R-α-pinene (1.04-2.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 25 publications
2
14
0
Order By: Relevance
“…The high quantity of monoterpenes followed by sesquiterpenes in the present study, with limonene as the major constituent of the C. reticulate, C. reticulata × C. sinensis , C. aurantiifolia and C. limon oils, is in agreement with data published on samples collected in other locations of Brazil for oranges (Badawy, Taktak, & El‐Aswad, ) and limes/lemons (Amorim et al, ; Gomes et al, ). The abundance of monoterpenes with limonene as the major component of Citrus oils has also been reported for samples from other countries, such as C. aurantiifolia in Vietnam (Dang et al, ), Cameroon (Tchameni et al, ), India (Fagodia, Singh, Batish, & Kohli, ) and Australia (Mirzaei‐Najafgholi, Tarighi, Golmohammadi, & Taheri, ); C. limon in India (Jain & Sharma, ) and Iran (Ghoorchibeigi et al, ); and C. reticulate in Vietnam (Dang et al, ), China (Tao, Jia, & Zhou, ), Pakistan (Zia et al, ), Nigeria (Ayoola et al, ) and Egypt (Hamdan, Mohamed, & El‐Shazly, ).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The high quantity of monoterpenes followed by sesquiterpenes in the present study, with limonene as the major constituent of the C. reticulate, C. reticulata × C. sinensis , C. aurantiifolia and C. limon oils, is in agreement with data published on samples collected in other locations of Brazil for oranges (Badawy, Taktak, & El‐Aswad, ) and limes/lemons (Amorim et al, ; Gomes et al, ). The abundance of monoterpenes with limonene as the major component of Citrus oils has also been reported for samples from other countries, such as C. aurantiifolia in Vietnam (Dang et al, ), Cameroon (Tchameni et al, ), India (Fagodia, Singh, Batish, & Kohli, ) and Australia (Mirzaei‐Najafgholi, Tarighi, Golmohammadi, & Taheri, ); C. limon in India (Jain & Sharma, ) and Iran (Ghoorchibeigi et al, ); and C. reticulate in Vietnam (Dang et al, ), China (Tao, Jia, & Zhou, ), Pakistan (Zia et al, ), Nigeria (Ayoola et al, ) and Egypt (Hamdan, Mohamed, & El‐Shazly, ).…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, the yields in the present study for the mandarin/tangerine oils (C. reticulate and C. reticulata × C. sinensis) were higher than those reported for samples collected in Faisalabad, Pakistan, bySadaf, Shahid, and Iqbal (2009), who attributed the lower yield (0.18 ± 0.03%) to the ripeness of the fruit. Gomes et al (2014) reported higher yields that those found in the present study for C. aurantiifolia and C. limon grown in Lavras, Brazil, whereas Ghoorchibeigi, Larijani, Azar, Zare, and Mehregan, (2017) and Tchameni, Mbiakeu, Sameza, Jazet, and Tchoumbougnang (2018) reported lower yields than those found in the present investigation for samples of C. aurantiifolia and C. limon collected in Iran and Cameroon, respectively.The high quantity of monoterpenes followed by sesquiterpenes in the present study, with limonene as the major constituent of the C. reticulate, C. reticulata × C. sinensis, C. aurantiifolia and C. limon oils, is in agreement with data published on samples collected in other locations of Brazil for oranges(Badawy, Taktak, & El-Aswad, 2017) and…”
supporting
confidence: 93%
See 3 more Smart Citations